Mental functionality tests to rate rehabilitative training effects in racing skiers' training systems - Dron, A. Y.; Gibadullin, I. G.; Kasumov, K. M.-R. (Theory and Practice of Physical Culture, 2017)
The study considers benefits of rehabilitative trainings for beginner racing skier groups as verified by the mental functionality tests. Subject to the study were 30 beginner racing skiers. The tests were performed ante meridiem since the rates are normally the most stable at this time of the day. A variety of mental functionality rating tests were made using the computerised NS-Psychotest.NET system (Neurosoft, Moscow), including the following: simple visual motor response (SVMR) test; tapping test; and response to moving object (RMO) test.